Performance recovery of creative sector industries: Strengthening management literacy and digital business innovation - Wahyudiono; Yustinus Budi Hermanto; Soffia Pudji Estiasih; Aminatuzzuhro (Journal of Innovation and Entrepreneurship, 2024)
This study examined the effect of strengthening management literacy on digital business innovation and accelerating performance recovery and examined the impact of digital business innovation on accelerating performance recovery. This study is explanative/associative research accompanied by hypothesis testing. The unit of analysis in this study was creative industry entrepreneurs, with a total population of 354. Sampling in this study used purposive sampling with specific criteria and obtained 194 as a sample size, after which they were referred to as respondents. Path analysis results show that strengthening management literacy directly and significantly influences digital business innovation and accelerates performance recovery; digital business innovation directly and substantially influences the acceleration of performance recovery in the creative industry sector. The findings of this study indicate that strengthening management literacy, which is carried out in a structured and massive manner, will encourage innovative behavior in implementing digital business. Digital business innovation will spur business activities to become more effective, because they are not limited by space and time.
Keywords: 650; Business; Digital; Literacy; Management; Performance